Herbal Medicine–Dream Unresolved - Singh, Dr. Amritpal (Pharmacognosy Reviews)
Herbal Medicine is defined as branch of science in which plant based formulations are used to alleviate the diseases. It is also known as botanical medicine or phytomedicine. Lately phytotherapy has been introduced as more accurate synonym of herbal or botanical medicine. Recently treatment of diseases with herbal medicine has been addressed as phytopharmacotherapy. Recently herbal medicinal products have been included in dietary supplements. In the early twentieth century herbal medicine was prime healthcare system as antibiotics or analgesics were not available. With evident of allopathic system of medicine, herbal medicine gradually lost its popularity among people and it was based on the fast therapeutic actions of synthetic drugs. Almost a century has passed and it has witnessed limitations of allopathic system of medicine. Lately herbal medicine has gained momentum and it is evident from the fact that certain herbal remedies peaked at par with synthetic drugs.